2021
DOI: 10.3390/parasitologia1010003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neonicotinoid Exposure on the Life History Traits and Susceptibility to Plasmodium Infection on the Major Avian Malaria Vector Culex pipiens (Diptera: Culicidae)

Abstract: Culex pipiens complexes play an important role in the transmission of a wide range of pathogens that infect humans, including viruses and filarial worms, as well as pathogens of wildlife, such as the avian malaria parasite (Plasmodium spp.). Numerous biotic and abiotic stresses influence vector-borne pathogen transmission directly, through changes in vector density, or indirectly by changing vector immunocompetence, lifespan, or reproductive potential. Among these stresses, mosquito exposure to sublethal doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 91 publications
(132 reference statements)
0
2
0
Order By: Relevance
“…Many studies that investigated the effects of sublethal concentrations of pesticides on larval mosquitoes have reported that the physiology of an individual is not reset during metamorphosis to enable it to negate these effects in adults [80,81]. The effects of physiological stressors during the immature developmental stage on the adult can also be difficult to interpret, as they may have multiple outcomes, such as longer development times, male-biased sex ratios, and higher emergence rates and body sizes [82][83][84][85] or they offer null impacts, depending on the xenobiotics [86,87].…”
Section: Sublethal Exposure Of Larvae To Insecticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies that investigated the effects of sublethal concentrations of pesticides on larval mosquitoes have reported that the physiology of an individual is not reset during metamorphosis to enable it to negate these effects in adults [80,81]. The effects of physiological stressors during the immature developmental stage on the adult can also be difficult to interpret, as they may have multiple outcomes, such as longer development times, male-biased sex ratios, and higher emergence rates and body sizes [82][83][84][85] or they offer null impacts, depending on the xenobiotics [86,87].…”
Section: Sublethal Exposure Of Larvae To Insecticidesmentioning
confidence: 99%
“…Studies have been carried out considering the interaction between adult mosquitoes derived from exposed larvae and malaria-causing parasites [86,87,94]. For instance, the exposure of Culex pipiens to the neonicotinoid imidacloprid did not affect the life history traits of individuals nor the susceptibility of adults to infection by avian malaria parasite (Plasmodium gallinaceum) [86]. The exposure of larvae of Cx.…”
Section: Sublethal Exposure Of Larvae To Insecticidesmentioning
confidence: 99%